{5- Endo-trig Radical Cyclizations: Disfavored or Favored Processes?} - Chatgilialoglu, Chryssostomos; Ferreri, Carla; Guerra, Maurizio; Timokhin, Vitaliy; Froudakis, Georgios; Gimisis, Thanasis (J. Am. Chem. Soc., 2002)
Relative kinetic data were determined for the 5-endo-trig cyclization of radical 12 compared to hydrogen abstraction from (TMS) 3SiH in the temperature range of 344-430 K, which allows for the estimation of a rate constant of 2 × 10 4 s -1 at 298 K with an activation energy of ca. 9 kcal/mol for the cyclization process. The 5-endo-trig cyclization of a variety of radicals that afford five-membered nitrogen-containing heterocycles was addressed computationally at the UB3LYP/6-31G* level. The 5-endo vs 4-exo mode of cyclication and the effect of delocalization of the unpaired electron in the transition state were investigated. Because the ring formed during cyclization contains five sp 2 centers, electrocyclization via a pentadienyl-like resonance form was also considered. For comparison, similar calculations were performed for 4-penten-1-yl and related radicals. The factors that affect the activation energies of homolytic 5-endo-trig cyclization were determined. In the absence of steric or conformational effects, the endo cyclization to form the five-membered ring was strongly favored over exo cyclization to form the four-membered ring not only on thermodynamic grounds but also kinetically. When a substituent on the double bond was able to delocalize the unpaired electron in the transition state of the 4-exo path, the two modes of cyclization became kinetically comparable. These results have an important bearing on the generalization of the Baldwin-Beckwith rules, which classified the 5-endo-trig radical cyclization as a "disfavored" process.